Theoretical System of Contact-Mode Triboelectric Nanogenerators for High Energy Conversion Efficiency - Chen, Huamin (Nanoscale Res Lett, 2018)
As the rapid expansion of next-generation electronics, portable and efficient energy sources has become one of the most important factors impeding the market development. Triboelectric nanogenerators (TENGs) are a potential candidate for its unsurpassed features. Herein, we deeply analyzed the power and conversion efficiency of contact-mode TENGs considering the whole energy conversion process. Firstly, reaching beyond the conventional analysis, a compressive force was introduced to derive a more versatile motion profile, which provided a better understanding of the working principle of contact-separation process. Then, we deeply analyzed the influence of various parameters on its performance. Especially, the maximum efficiency TENGs can be obtained under optimum force. It is realistic and useful for more efficient TENGs. Furthermore, this research stands a good chance of establishing standards for quantifying the efficiency of TENGs, which lays the basis for the further industrialization and multi-functionization of TENGs technology. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s11671-018-2764-2) contains supplementary material, which is available to authorized users.